2021
DOI: 10.3389/fnmol.2021.661728
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Impairs Dendritic Trafficking of Golgi-Like Organelles in the Early Phase Preceding Neurite Atrophy: Rescue by Mirtazapine

Abstract: Neurite atrophy with loss of neuronal polarity is a pathological hallmark of Alzheimer’s disease (AD) and other neurological disorders. While there is substantial agreement that disruption of intracellular vesicle trafficking is associated with axonal pathology in AD, comparatively less is known regarding its role in dendritic atrophy. This is a significant gap of knowledge because, unlike axons, dendrites are endowed with the complete endomembrane system comprising endoplasmic reticulum (ER), ER–Golgi interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…It has been demonstrated in brain tissue samples and experimental models of AD with Aβ that the abnormal rearrangement of the GA affects cell morphology and several physiological functions [97][98][99]. It had been reported that Aβ can alter the GA indirectly through the abnormal acetylation of cytoskeleton proteins, as well as by the induction of Tau hyperphosphorylation and cytoskeleton destabilization, which in turn disrupt intracellular transport [27,100,101]. Rodriguez-Cruz and collaborators recently reported similar data but using Tau protein overexpression as a pathological stimulus in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated in brain tissue samples and experimental models of AD with Aβ that the abnormal rearrangement of the GA affects cell morphology and several physiological functions [97][98][99]. It had been reported that Aβ can alter the GA indirectly through the abnormal acetylation of cytoskeleton proteins, as well as by the induction of Tau hyperphosphorylation and cytoskeleton destabilization, which in turn disrupt intracellular transport [27,100,101]. Rodriguez-Cruz and collaborators recently reported similar data but using Tau protein overexpression as a pathological stimulus in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…To check if the AβOs obtained after 24 h of oligomerization could induce cytotoxicity in SH-SY5Y cells, as many reports suggest [23][24][25], we analyzed the cell viability 3, 12, 24, 48, 72, and 96 h after exposure to 10 µM AβOs, a concentration previously determined by other authors [26][27][28]. At the end of the exposure time, we used the MTT reduction assay to evaluate cell viability.…”
Section: Aβo Toxicity In Sh-sy5y Cell Cultures Is Time-dependentmentioning
confidence: 99%
“…Furthermore, it is known that this antidepressant drug acts on the gene expressions of pro-apoptotic (Bax and p53) proteins, reducing their expressions [11]. With the application of this drug, there is also evidence of reduced neurite atrophy, a phenomenon that is evidenced in depression [25][26][27]. By establishing a stress model that is similar to the oxidative stress that occurs in individuals with depression, the doors were opened to the studying of other compounds that may be able to reverse or attenuate this damage.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using human neuroblastoma cells, Flx was found to reduce intracellular Aβo concentration [ 15 ]. In contrast, mouse model studies on AD have shown that Flx can lower Aβ levels in brain tissue, cerebrospinal fluid, and serum, delaying cognitive decline [ 16 , 17 ]. Additionally, Mir has been reported to reverse neurite atrophy caused by Aβo [ 18 ], and Flx and Dlx have demonstrated antioxidant effects in animal brain tissue [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%